1999
DOI: 10.1111/j.1469-7793.1999.0143z.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cardiomyocyte relaxation and diastolic function in transgenic mice expressing slow skeletal troponin I in the heart

Abstract: To assess the specific functions of the cardiac isoform of troponin I (cTnI), we produced transgenic mice that expressed slow skeletal troponin I (ssTnI) specifically in cardiomyocytes. Cardiomyocytes from these mice displayed quantitative replacement of cTnI with transgene‐encoded ssTnI. The ssTnI transgenic mice were viable and fertile and did not display increased mortality or detectable cardiovascular histopathology. They exhibited normal ventricular weights and heart rates. Permeabilized transgenic cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
233
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(271 citation statements)
references
References 47 publications
31
233
5
Order By: Relevance
“…27,34 The strikingly similar calcium sensitivities in the t/t PTU and ϩ/ϩ PTU we report here may therefore indicate that cMyBP-C does not significantly affect calcium sensitivity of isometric tension, just as cMyBP-C phosphorylation also does not affect calcium sensitivity. 17,18 A reduction in isometric tension with increasing [P i ], as observed in the myofilaments lacking cMyBP-C, can be explained by a higher probability of reversal of the forceproducing power stroke of the acto-myosin crossbridge, which would occur with a higher probability of a backreaction of the phosphate-release step. 35,36 Our finding that a lack of cMyBP-C furthermore increases the characteristic frequency and the phosphate-dependence of oscillatory work production is intriguing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,34 The strikingly similar calcium sensitivities in the t/t PTU and ϩ/ϩ PTU we report here may therefore indicate that cMyBP-C does not significantly affect calcium sensitivity of isometric tension, just as cMyBP-C phosphorylation also does not affect calcium sensitivity. 17,18 A reduction in isometric tension with increasing [P i ], as observed in the myofilaments lacking cMyBP-C, can be explained by a higher probability of reversal of the forceproducing power stroke of the acto-myosin crossbridge, which would occur with a higher probability of a backreaction of the phosphate-release step. 35,36 Our finding that a lack of cMyBP-C furthermore increases the characteristic frequency and the phosphate-dependence of oscillatory work production is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] The possible effects of cMyBP-C and of its phosphorylation on actomyosin crossbridge kinetics are not yet clear, 15,16 although its phosphorylation does not apparently affect the tension-pCa relationship. 17,18 The effect of cMyBP-C itself on the tensionpCa relationship has so far proved equivocal: the chemical extraction of cMyBP-C from rat cardiomyocytes enhances calcium activation, 16 whereas the absence of cMyBP-C in mouse myocardium inhibits, 19 does not affect, 11 or enhances 9 calcium activation. Some of the discrepancies in these observations may be caused by differing experimental preparations and methods and/or the variable shifts of sarcomeric protein isoforms, such as myosin heavy chain (MHC) isoform from ␣-MHC to ␤-MHC, that occur in mouse models deficient in cMyBP-C. 19,20 Curiously, in both mouse models so far demonstrated to lack sarcomeric cMyBP-C, the LV is dilated, systolic elastance is dramatically reduced compared with normal, and the duration of ejection phase is similarly abbreviated.…”
mentioning
confidence: 99%
“…We chose the slow skeletal isoform for these studies inasmuch as it is naturally expressed in the embryonic/neonatal period. Hearts of TG-ssTnI mice had slower relaxation kinetics, depressed effects of β-adrenergic stimulation [8], and protection against acidosis [9,10] and ischemia/reperfusion injury [11]. All of these properties are properties of preparations from neonatal rat hearts, and indicated that the special cardiac function in the neonatal period is importantly controlled by the isoform of TnI.…”
Section: Specific Modifications In Troponin I Affect the Dynamics Andmentioning
confidence: 99%
“…Although it had been reported that phosphorylation of this region depressed sarcomeric response to Ca 2+ and increased cross-bridge kinetics [2,3], studies with transgenic models have provided the strongest evidence for a critical role of Tn, especially cTnI, in cardiac function. The first series of studies were carried out with a transgenic mouse model expressing ssTnI (TG-ssTnI) to the exclusion of cTnI in the cardiac compartment [8]. We chose the slow skeletal isoform for these studies inasmuch as it is naturally expressed in the embryonic/neonatal period.…”
Section: Specific Modifications In Troponin I Affect the Dynamics Andmentioning
confidence: 99%
“…Permeabilized cardiomyocytes from transgenic mice overexpressing STnI in the heart displayed an increased Ca 2+ sensitivity of force and a lack of responsiveness to PKA phosphorylation (48). It has been demonstrated that different TnI isoforms contribute to different responses of cardiac vs. fast skeletal vs. slow skeletal muscles to acidic pH, with the CTnI isoform contributing the most to the susceptibility of the muscle to acidosis-dependent deactivation (49).…”
Section: Troponin Imentioning
confidence: 99%